Implementasi Project Quality Management dan Perancangan Proses Bisnis Pada Milestone First Years Inspection dan di Proyek Konstruksi di PT PLN Nusantara Power - Batubara, Nasep Nirwan; Nugraha, Evan; Suryana, Hendy; Patra, Oviyan (Publikasi Indonesia, 2025)
This study aims to evaluate the implementation of Project Quality Management (PQM) in the First Year Inspection (FYI) milestone of the Muara Tawar Add-On Combined Cycle Power Plant (PLTGU) Block 2 project, and to design an integrated business process using the lean construction approach. A mixed-methods research design was applied, combining observation, in-depth interviews, and document analysis. The findings reveal that the PQM implementation, based on PMBOK 7 principles—namely Quality Planning, Quality Assurance, and Quality Control—was mostly at a “partial fit” level due to non-standardized documentation and delays in corrective actions. The FYI business process was mapped using Value Stream Mapping (VSM) and Big Picture Mapping (BPM) to classify value-added (VA), non-value-added (NVA), and necessary non-value-added (NNVA) activities. Of the 23 total activities analyzed, 14 were identified as value-added, while 2 were classified as wasteful. The main causes of inefficiency included waiting time, unnecessary inventory, and excessive transportation. These were mitigated through the integration of collaborative spreadsheets and improved stakeholder coordination. The study emphasizes the importance of having a single source of truth in defect monitoring among project stakeholders (owner, contractor, consultant) to enable better communication and decision-making. Results demonstrate that the resolution of FYI pending items was completed earlier than the planned schedule, validating the effectiveness of integrating lean construction tools to enhance PQM outcomes in power plant construction projects.